Boosting photocatalytic water oxidation by surface plasmon resonance of AgxAu1−x alloy nanoparticles. (September 2021) - Haider, Rida Shahzadi; Wang, Shengyang; Gao, Yuying; Malik, Anum Shahid; Ta, Na; Li, Hao; Zeng, Bin; Dupuis, Michel; Fan, Fengtao; Li, Can
Abstract: Surface plasmon resonance (SPR) induced photocatalysis with multi-metallic nanoparticles stays indistinct, especially in photo-induced water oxidation reaction. Herein, we report a strategy of engineering band structure by noble metal alloying (Agx Au1−x ). The modulated composition of AgAu alloy nanoparticles loaded on rutile TiO2 to selectively tune SPR wavelengths and d-band position. We found that SPR-induced water oxidation activity varies as a function of the ratio of Au and Ag in Agx Au1−x /TiO2 photocatalysts, exhibiting"volcano-like" relationship between the oxygen evolution production rate and the metal-composition. The Ag0.6 Au0.4 /TiO2 photocatalyst shows superior water oxidation performance about 3-folds of individual Ag and Au. Photoemission spectra (PES) of alloy are in correlation with density of states, revealing the sensitivity of d-band onset energies and SPR excitation wavelengths. Furthermore, surface-photovoltage (SPV) response of alloy signifies the superiority of alloy in interfacial charge separation of hot carriers. Density functional theory (DFT) calculations validate the experimental results by revealing complex AgAu alloy-semiconductor (Ti-O-Au-Ag) for oxygen evolution along with electrodynamic simulations to trace distribution of electric-field components. This work demonstrates critical role of d-band tuning across alloy composition for boosting catalytic fraction through the integrated effects of light absorption, Schottky barrier height and d-band position of the plasmonic photocatalysts. Graphical Abstract: In surface plasmon induced photocatalyst, both optical and electronic properties are important for eventual photocatalytic efficiency. For photocatalytic water oxidation reaction, the stability of plasmonic metal is also a critical issue. In this work, an alloyed Agx Au1−x /TiO2 plasmon-induced water oxidation photocatalyst is employed as a model system to study the structure-function relationship. We demonstrated that a three-in-one photocatalyst, i.e. efficient visible-light absorption, suitable electronic structure and high-stability, could be achieved through alloy components adjustment. ga1 Highlights: Simple chemical approach for compositional tuning of Agx Au1−x alloy across SPR wavelengths of electromagnetic spectrum. Enhancement in plasmon-induced water oxidation activity achieved by tuning of d-band structure and Schottky barrier height. SPV confirms efficient charge separation across Ag0.6 Au0.4 /TiO2 photocatalyst. DFT calculation confirms that noble metal as an active may increase photocatalytic OER performance.